Legal Issues Concerning Consumer Protection in Metaverse Operation in Nigeria: Taking a Leap from Uganda: Masalah Hukum Terkait Perlindungan Konsumen dalam Operasi Metaverse di Nigeria: Mengambil Langkah Maju dari Uganda - Atagamen Aidonojie, Paul; Chetachukwu Aidonojie, Esther; Obieshi, Eregbuonye; Odeyinka-Apantaku, Olawumi; Collinsd, Ekpenisi (Perspektif Hukum, 2025)
The Metaverse concept is a unique and trending digital platform, that has transformed commercial and social activities. Despite the prospect of Nigerian commercial activities in the Metaverse, it presents some unique challenges for consumers. Concerning this, the study examines the legal issues surrounding consumer protection in the Metaverse, to adopt possible legal ideas from Uganda’s experience, the study adopted a hybrid method of study, and 317 questionnaires were distributed to respondents residing within Nigeria. The results were analyzed with the aid of a descriptive and analytical approach. The study reveals that the metaverse concept provides significant prospects and potential for consumers. However, there are legal and social issues consumers may encounter. These challenges include a lack of legal measures in safeguarding consumer rights in the metaverse, the incidence of fraudulent activities by fraudsters, and several other challenges. It was therefore concluded and recommended that, for an effective operation of the metaverse that would not violate consumer rights, there is a need to incorporate an effective legal framework that will safeguard consumer interest. In this regard, the study recommends Uganda’s consumer protection laws as a model for the Nigerian government to adopt in safeguarding consumer commercial activities in the metaverse.